Decommissioning Research Needs for Offshore Oil and Gas Infrastructure in Australia - Melbourne-Thomas, Jess; Hayes, Keith R.; Hobday, Alistair J.; Little, L. Richard; Strzelecki, Joanna; Thomson, Damian P.; van Putten, Ingrid; Hook, Sharon E. (Frontiers in Marine Science, 2021)
When offshore oil and gas infrastructure is no longer needed, it is either removed, partially removed, left in place, or left in place but repurposed. These processes are collectively referred to as decommissioning. Australian legislation requires oil and gas companies to develop acceptable plans for the safe removal of all offshore infrastructure at the end of a project’s life. Over the next 50 years, the liability for this decommissioning in Australia is expected to exceed US$45 billion. Unlike countries such as Norway, the United Kingdom and the Netherlands, Australian decommissioning activities are in their infancy, with only three cases (to date) in Commonwealth waters where infrastructure has been left in place or partially removed as part of decommissioning. Differences between the Australian marine environment and that of other regions around the world where decommissioning-related research is better progressed include very low sedimentation rates, both tropical and temperate habitats, different species composition, low primary production, and frequent tropical cyclones, as well as unique sociodemographic and cultural characteristics. Accordingly, the outcomes of the decision support tools used in other regions to identify preferred decommissioning options may not be equally applicable in Australia. Here we describe research to support risk and impact assessment for offshore decommissioning in Australia, where full removal of infrastructure is the ‘base case’ regulatory default, but other options including partial removal and/or repurposing might provide similar or better outcomes when environmental, social, economic and seafood safety aspects are considered. Based on our review we propose an integrated framework for research needs to meet legislative requirements for decommissioning and identify research gaps that need to be addressed to inform decision-making for decommissioning in the Australian context.